Bioethics and Law - D'Agostino, Francesco (Medicina e Morale, 1993)
The author starts with the observation that there isn't a "biolegal" science and that it is necessary in the area of bioethical reflection in order to propose legal indications. In order to carry this out he considers useful to first define the epistemic code of the Law. The Author believes that only the model defined as "relational", which sees in the law the defence system of the rights of a person who, by bis nature, has relationships with other people, is suitable for the construction of a bio lega! science. Consequently the author deduces that the law can only guarantee values that are coherent with the logic of relationships: that it does not protect only it but also the antologie parity of the persons and that, finally, its area is the system of social actions. The study also enunciates, what, according to the author, are the ambits of" biolaw", demonstrating the correspondence of the model outlined from a practical point of view, and applying it to two controversial current themes, euthanasia and in vitro fertilization.